Insights into the phase diagram of the CrMnFeCoNi high entropy alloy. (15th April 2015) - Laurent-Brocq, Mathilde; Akhatova, Alfiya; Perrière, Loïc; Chebini, Siham; Sauvage, Xavier; Leroy, Eric; Champion, Yannick
Graphical abstract: Abstract: In order to study the thermodynamics of high entropy alloys, the evolution of the structure and microstructure of the equimolar CrMnFeCoNi high entropy alloy was investigated during processing under varying conditions (cooling rate and annealing duration). For the very first time, a true solid-solution down to the atomic scale was evidenced in an HEA by atom probe tomography. It was shown that this face-centered cubic single-phase solid solution is the high temperature stable state of the equimolar CrMnFeCoNi alloy. By analogy with completely miscible binary alloy, the CrMnFeCoNi HEA can be described by a schematic phase diagram of the CrFeCo–MnNi system consisting of a liquidus and a solidus, with a partition coefficient of 0.74. When the liquid phase is cooled down, dendrites enriched in Co, Cr and Fe are formed and afterward interdendrites enriched in Mn and Ni solidify. The solid solution can be reached either by a fast enough cooling or by annealing the dendritic structure, for example at 1100 °C for 1 h. A method to optimize the temperature and duration of an annealing of homogenization is proposed.